Automatic CV updating system - Liu, Xueqing (Nanyang Technological University, 2020)
This project aim to develop an academic CV management web application with automatic information-appending capability. Main functions of this web application will enable users to update their CV online by key in relevant information to the web application and export their CVs with the most up-to-date information appended at the top of corresponding sections on the CV.